The state liability derived from the inactivity of the public administration in the Peruvian ordinance: notes for the study of its legal regime - Huapaya Tapia, Ramón (Universidad Nacional del Litoral, 2019)
The authors propose the revision of the legal problem of administrative inactivity in the Peruvian legal system and the consequences of the responsibility derived from said omission, understood as the unlawful breach of a legal duty of action or of the administrative functions assigned to public entities. For this, the concept of administrative inactivity, its typology and the patrimonial responsibility attributable to the Public Administration as a result of such omission, inertia or passivity is reviewed. The analysis concludes with the procedural problem of the requirement of the patrimonial responsibility to the Public Administration, derived from the notable deficiencies of Peruvian Law that regulates the contentious-administrative process.